Work relationships and their impact on job performance - Bourguibat, Mokhtar; Farfar, Djamel (The International tax journal, 2025)
The study aims to shed light on work relationships and their impact on job performance through a case study of educational institutions in the camp. To accomplish this study, we followed a descriptive analytical approach and utilized interviews and observations as primary means of data collection on the subject of the study, The representative sample of the research community included 30 workers in educational institutions. Ultimately, the study reached several conclusions, the most important of which is that work relationships either positively or negatively affect the level of job performance of workers. The better the work relationships are based on solidarity, cooperation, and understanding, the higher the level of job performance; conversely, when work relationships are characterized by conflict and dispute, the level of job performance of the workers declines.